Rock mass slope stability analysis based on terrestrial LiDAR survey on selected limestone hills in Kinta Valley, Perak / Muhammad Afiq Ariff Mohd Hellmy - Muhammad Afiq Ariff , Mohd Hellmy (2020)
The use modern mapping technology is necessary in assessing slopes and cliffs, especially in tropical countries as it is mostly inaccessible and covered with thick vegetation which restricts the conventional data collection only at the base of the cliff. Overhanging and sub-vertical characteristics of limestone hills in Kinta Valley together with highly fractured and day-lighting joints increase the possibility of rock slope failure. The main objective of this research is to assess the stability and rock mass properties of the limestone hills in Kinta Valley based on the output provided by terrestrial LiDAR and scanline survey. Terrestrial laser scanning (TLS) helps engineers and geologist to collect a high numbers of discontinuity data where it is inaccessible for manual data measurement. A total number of about 14 cliffs on 4 limestone hills were assessed. Gunung Lang and Kek Lok Tong show major potential failure trending towards east, Gunung Lanno towards southwest, Kwan Yin Tong towards west, and Gunung Cheroh with three directions of failure which are pointed towards the south, southwest and southeast direction. The integration of LiDAR method with the manual compass clinometer has become a better approach to assess the stability of limestone hills and other rock slope in the possible future.